SAKTI Implementation and the Reform of Public Financial Management Through E-Government - Isidorus Anung Prabadhi; Triyuni Soemartono; Johanes Basuki; Gatot Hery Djatmiko (International Journal of Qualitative Research, 2026)
The digitalisation of public financial management in Indonesia has progressed through the development of integrated financial information systems, including the Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI) at the work-unit level. This article analyses the implementation of SAKTI at the Immigration Polytechnic as part of public financial management reform through e-government. The study aims to examine how SAKTI is implemented in financial management practices, identify technological and organisational challenges affecting its effectiveness, and formulate strategic measures to strengthen its contribution to efficiency, transparency, accountability, and evidence-based decision-making. This study employed a qualitative single case study approach using semi-structured interviews and document analysis. The DeLone and McLean Information Systems Success Model was used as an analytical framework to organise findings related to system quality, information quality, service quality, system use, user satisfaction, and net benefits. The findings indicate that SAKTI has improved the integration, standardisation, traceability, and auditability of financial transactions. However, the implementation still faces socio-technical challenges, including unstable internet connectivity, system slowdowns during peak workload periods, limited continuous training, uneven digital literacy, and the need for more responsive technical support. The study suggests that SAKTI implementation should be strengthened through improved technical infrastructure, tiered and continuous capacity-building, responsive support mechanisms, stronger leadership commitment, and more strategic use of financial data for institutional decision-making.